PEREMPUAN DALAM PERSPEKTIF PENGARANG LAKI-LAKI NOVEL GADIS PANTAI - Gunawas, Risal; Anshari, Anshari; Azis, Abdul (Wahana Literasi: Journal of Language, Literature, and Linguistics, 2022)
The purpose of this study is to describe the existence of women in the perspective of male authors in terms of existentialist, liberal feminism studies and the differences between the two theories from the novel Gadis Pantai by Pramoedya Ananta Toer. This research is a type of qualitative descriptive research so that the preparation of the design is designed based on the principles of qualitative research methods, namely collecting, processing, reducing, analyzing, and presenting data objectively or in accordance with the facts of the data. The source of the data in this research is the novel by Pramoedya Ananta Toer, entitled Gadis Pantai. The results showed that; (1) the author's perspective in reflecting on the main character of existentialist feminism so that there is resistance in the social sphere regarding women's rights in the colonial era; (2) the author's perspective from liberal feminism, namely the respect for obedient men to women by looking at their social status; and (3) the difference between existentialist feminism and liberal feminism lies in the right to exist and freedom of women in the family and social spheres. The author's factor in reflecting on women's resistance in the novel Gadis Pantai is to fight Javanese feudalism which was greedy for power in the colonial era.